Indoors or Outdoors? An International Exploration of Owner Demographics and Decision Making Associated with Lifestyle of Pet Cats - Rachel Foreman-Worsley; Lauren R. Finka; Samantha J. Ward; Mark J. Farnworth (Animals, 2021)
Outdoor access for owned domestic cats (Felis catus) is a divisive issue. Cat safety, mental and physical wellbeing, infectious diseases, and wildlife depredation are cited as factors influencing owners; however, the degree of consideration each factor receives has not been quantified. This study (i) analysed which demographic variables are associated with greater odds of cats having indoor or outdoor lifestyles, (ii) identified which factors owners consider when making a choice on lifestyle and any regional variations, and (iii) identified if owners consider the different lifestyle options available and recognise their associated benefits. A series of online surveys were used for data collection. Binary logistic regression models were used to generate odds ratios assessing if demographic variables were significantly associated with cat lifestyle. Quantitative analysis of factors considered when deciding on cat lifestyle was accompanied by a thematic analysis of rich-text open-ended responses, providing nuanced insight into the rationale and elucidating additional factors considered. Of the demographic variables tested, 10/12 were significantly associated with lifestyle. Variables with higher odds of indoor-only lifestyles were owners being 26–35 years old, multi-cat households, junior cats, pedigree cats or unknown pedigree status, cats with health issues, living in city centres or urban areas, or living in the United States, Canada, Australia, or New Zealand. Variables with higher odds of indoor-outdoor lifestyles were owners being 46–55 years old or 56+ years old, households with residents 17 years old or under, male cats, and cats being mature or senior. Road traffic concerns were the most cited reason for keeping indoor-only cats across all global regions. The second-most cited reason varied regionally. For Europe, it was protection from people. For the USA and Canada, the reason was protection from wildlife, and for Australia and New Zealand, to prevent hunting. Indoor-outdoor cat owners cited most frequently the benefits to their cat’s mental health. Over two-thirds of owners did not consider the alternative lifestyle for their cat. These data give insight into the priorities of cat owners with regards to feline wellbeing, feline safety, and wildlife depredation, helpful for individuals or organisations working with human behaviour change. They provide evidence that the numbers of indoor-only cats are likely to rise with increasing urbanisation. Finally, the data identify cat populations who may be at risk of compromised welfare due to unsuitable, or under-researched, lifestyles.